2020
DOI: 10.1590/0034-7167-2019-0310
|View full text |Cite
|
Sign up to set email alerts
|

Organizational flow chart of home care for children with special health care needs

Abstract: Objective: To develop a workflow protocol for Home Care (HC) services in the HC2 modality for children with special health care needs (CSHCN) in the state of Parana. Method: Quantitative, descriptive, exploratory, multiple case studies. Data was collected with professionals from the eight home care services in Parana. Data were analyzed using the Strengths, Weaknesses, Opportunities and Threats (SWOT) methodology, from which a 5W2H method of action plan was developed, resulting in a flow chart. Results: Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
1
0
7
Order By: Relevance
“…Analisando os diagnósticos das CRIANES do estudo e suas demandas de cuidados, a maioria se originou de fatores perinatais. Assim, são classificadas majoritariamente como AD2, por demandarem cuidados específicos, como a utilização de sondas enterais, gastrostomia, 13 Um estudo identificou os principais desafios dos cuidadores familiares, 14 pois os cuidados múltiplos, complexos e contínuos que as famílias realizam no domicílio demandam preparo emocional e técnico. Um dos principais desafios das famílias é o despreparo para cuidar da criança no domicílio.…”
Section: Discussionunclassified
“…Analisando os diagnósticos das CRIANES do estudo e suas demandas de cuidados, a maioria se originou de fatores perinatais. Assim, são classificadas majoritariamente como AD2, por demandarem cuidados específicos, como a utilização de sondas enterais, gastrostomia, 13 Um estudo identificou os principais desafios dos cuidadores familiares, 14 pois os cuidados múltiplos, complexos e contínuos que as famílias realizam no domicílio demandam preparo emocional e técnico. Um dos principais desafios das famílias é o despreparo para cuidar da criança no domicílio.…”
Section: Discussionunclassified
“…These results are similar to those found in Paraná. 13 One study identified the main challenges of family caregivers 14 because the multiple, complex, and continuous care that families perform at home requires emotional and technical preparation. One of the families' main challenges is the unpreparedness to care for the child at home.…”
Section: Discussionmentioning
confidence: 99%
“…2 Os medicamentos e os exames de média complexidade deveriam ser amplamente oferecidos para o grupo de Crianes, mas um estudo corrobora os resultados aqui expostos ao demonstrar uma oferta insuficiente de exames de imagem e medicamentos de uso contínuo. 24 Essas barreiras encontradas para o cuidado induzem as famílias a requerer seus direitos por via judicial, representado pelo movimento e desejo de cuidar. 2 Pesquisa realizada em quatro regiões do Brasil reforçou que o elevado número de processos judiciais por parte das famílias e o excesso de encaminhamentos às outras esferas de atenção são resultantes do despreparo dos profissionais ante as demandas exigidas por Crianes, 9 assim como relatado pelos participantes.…”
Section: Discussionunclassified